Base catalyzed sustainable synthesis of phenyl esters from carboxylic acids using diphenyl carbonate1. Issue 65 (16th July 2015) - Kreye, Oliver; Meier, Michael A. R.
<x xml:space="preserve">Abstract</x> Phenyl esters were obtained in moderate to high yields by reaction of aliphatic and aromatic carboxylic acids with one equivalent of diphenyl carbonate in the presence of catalytic amounts of tertiary amine bases, under neat conditions at elevated temperatures (>100 °C).